KAJIAN INVESTIGASI INTERNAL ACCIDENT DAN INCIDENT TERHADAP KESELAMATAN PENERBANGAN DI PERUM LPPNPI MAKASSAR AIR TRAFFIC SERVICE CENTRE (MATSC) - Georgio Dimas Wiweka Prakoso Palendeng; Sudrajat; Paramita Dwi Nastit (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Investigation is the activity of collecting, writing, editing, and publishing news that is investigative in nature, or a long and in-depth search of a case that is considered to have irregularities. In addition, the investigation is a search for confidential cases, and the agency responsible for carrying out the investigation is the NTSC (National Transportation Safety Committee). Based on the formulation of the problem, namely whether internal accident and incident investigations affect flight safety, which aims to determine whether or not an internal investigation has an effect on flight safety, especially by Air Traffic Controllers to transportation service users. The research method in this study the author uses qualitative descriptive research with literature and document studies as well as conducting interviews with several AirNav employees at Sultan Hasanuddin Airport Makassar. The result of this research is that by carrying out investigation activities, it is possible to minimize all factors that can cause an airplane accident (accident / incident), from the results of observations and interviews, the implementation process of the investigation in Makassar is more or less going well, although it still requires a few changes to minimize an incident that occurs and can affect flight safety at Sultan Hasanuddin Airport Makassar.